2017
DOI: 10.2174/1871527316666170413114210
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Aspects of Medical Use of Cannabidiol

Abstract: Pre-clinical evidence largely shows that CBD can produce beneficial effects in AD, PD and MS patients, but its employment for these disorders needs further confirmation from well designed clinical studies. CBD pre-clinical demonstration of antiepileptic activity is supported by recent clinical studies in human epileptic subjects resistant to standard antiepileptic drugs showing its potential use in children and young adults affected by refractory epilepsy. Evidence for use of CBD in PD is still not supported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 0 publications
0
55
0
Order By: Relevance
“…Cannabis chemovars ('strains') and medicinal cannabis products often contain significant levels of cannabidiol (CBD), a nonintoxicating cannabinoid with anxiolytic, anticonvulsant, and antipsychotic properties. [26][27][28] For example, the 'light cannabis' products that are legally available in a number of EU countries must contain less than 0.2% THC but may contain up to 40% CBD. 29 Medicinal cannabis products containing both THC and CBD include Nabiximols (Sativex), a buccal spray with a 1:1 ratio of THC and CBD, as well as commercially available cannabis botanicals and extracts 30 and homegrown illicit artisanal preparations.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis chemovars ('strains') and medicinal cannabis products often contain significant levels of cannabidiol (CBD), a nonintoxicating cannabinoid with anxiolytic, anticonvulsant, and antipsychotic properties. [26][27][28] For example, the 'light cannabis' products that are legally available in a number of EU countries must contain less than 0.2% THC but may contain up to 40% CBD. 29 Medicinal cannabis products containing both THC and CBD include Nabiximols (Sativex), a buccal spray with a 1:1 ratio of THC and CBD, as well as commercially available cannabis botanicals and extracts 30 and homegrown illicit artisanal preparations.…”
Section: Introductionmentioning
confidence: 99%
“…Athletes are known as early adopters of new and innovative modalities to aid in recovery and performance (Conrad et al 2019;Caine et al 2012), particularly since pain, insomnia, and anxiety are common and difficult to solve problems among athletes (Hainline et al 2017;Mann et al 2007;Halson 2014). Cannabis is a modality that has reportedly improved symptoms among sufferers of pain, insomnia, and anxiety (Stith et al 2019;Mannucci et al 2017), but has rarely been studied in the context of adult athlete use. Historically, cannabis use in athletes has typically been studied in the framework of abuse among adolescent, university, and elite athletes (Ware et al 2018;Buckman et al 2011;Peretti-Watel et al 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-clinical research showed CBD to be anticonvulsant in experimental animal models of epilepsy and to produce antipsychotic effects in experimental schizophrenia in humans [18,19]. Results from laboratory and human studies suggest that it could be a promising novel agent for central nervous system diseases, including schizophrenia [7] and epilepsy [20][21][22]. In humans, treatment with CBD is able to decrease the frequency of seizures showing a good risk/benefit profile [23,24].…”
Section: Introductionmentioning
confidence: 99%